Efektivitas Penggunaan Bokashi Blotong Tebu dan Pemberian Pupuk Organik Cair Kulit Nanas Terhadap Produktifitas Tanaman Kecipir (Psophocarpus tetragonolobus L.) - Muhammad Jusfar Simajuntak; Syahbudin Hasibuan; Maimunah Maimunah (Universitas Medan Area, 2019)
Cowpeas is becoming rare, hence it has to be planted again to some reasons. This research aims to know the growth and production of cowpeas with Bokashi use of sugarcane filter cake and liquid organic fertilizer pineapple skin that have been implemented at the Faculty of Agriculture Experimental Station Road PBSI Area Terrain 1 Terrain Estate, District Percut Sei Tuan from March to July 2019. Methods the research in this research is a randomized block design factorial, with 2 (two) treatment factors, namely: 1) factors bokashi cane filter cake (T) and Organic Liquid Fertilizer Factors pineapple skin (S), each treatment was repeated 2 times so that there are 32 experimental plots. Each experimental plot consisted of eight plants with four plant samples. The results of this research indicate that the use of Bokashi blotong cane very significant effect on the number of pods persample but did not significantly affect stem diameter, length of pods persampel, heavy pods persampel and production perplot, fertilizer liquid organic pineapple skin very significant effect on the number of pods persampel, but did not significantly affect stem diameter, persampel pod length, pod weight and production persampel perplot, a combination of the use of sugarcane filter cake bokashi organic fertilizer liquid and pineapple skin no real effect on the growth and yield of cowpeas.